Per un dizionario dell'italiano burocratico - Pace, Bruno (Verbum – Analecta Neolatina, 2017)
In this paper we present our research project which aims to create a dictionary of bureaucratic Italian. We start by defining the area of interest, and how it has been considered by linguists. We will see how bureaucratic terms are recorded in the main contemporary dictionaries. Then we illustrate how we intend to implement our work: we will build a corpus of selected texts, from which we will get the list of headwords, and plan the format for each entry and the general structure of our dictionary. We expect that this work may be useful in the studies of the bureaucratic language and may encourage further projects.